AKTIVITAS ANTIBAKTERI EKSTRAK BIJI LABU AIR (Lagenaria siceraria) TERHADAP Staphylococcus epidermidis, Staphylococcus aureus dan Escherichia coli - Silvi Nurafni; Siti Mariam; Kasriati (Jurnal Farmamedika (Pharmamedika Journal), 2016)
Lagenaria siceraria, known as water pumpkin seeds containing compounds alkaloids, phenolics, tannins, flavonoids and steroids. The above compounds are potentially as antibacterial. This research aims to know the effectiveness of the inhibition of the growth of the bacteria Staphylococcus epidermidis, Staphylococcus aureus and Escherichia coli. Based on the results of the research it is known that phytochemicals may be screening the content of water pumpkin seeds (Lagenaria siceraria) namely alkaloids, tannins, flavonoids, steroids and phenol. From the results of testing the effectiveness of antibacterial water pumpkin seed extract with ethyl acetate solvent, hexane and water is able to inhibit the growth of Staphylococcus epidermidis, Staphylococcus aureus and Escherichia coli. However the antibacterial activity of extracts of water pumpkin seeds using solvent hexane has a zone larger than drag the extract water pumpkin seeds using the solvent ethyl acetate and water. Comparison of antimicrobial activity of the solvent on the third with variation concentration of solvent shows a meaningful difference in inhibiting the growth of bacteria Staphylococcus epidermidis, Staphylococcus aureus and Escherichia coli. It can be seen from the p-value < 0.05 (p = 0.000).